2022
DOI: 10.3390/genes13122303
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Discovery for Meta-Classification of Melanoma Metastatic Progression Using Transfer Learning

Abstract: Melanoma is considered to be the most serious and aggressive type of skin cancer, and metastasis appears to be the most important factor in its prognosis. Herein, we developed a transfer learning-based biomarker discovery model that could aid in the diagnosis and prognosis of this disease. After applying it to the ensemble machine learning model, results revealed that the genes found were consistent with those found using other methodologies previously applied to the same TCGA (The Cancer Genome Atlas) data se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…And Huang et al confirmed that GABRD receptors indicated by T cells directly inhibit CD8 + T cells by participating in signal regulation ( Huang et al, 2022 ). Glutamate ionotropic receptor kainate type subunit 3 (GRIK3) and glutamate receptor ionotropic kainate-5 (GRIK5) are members of the glutamate kainate receptor family and play crucial roles in the neuroactive ligand-receptor interaction pathway ( Fang et al, 2021 ; Minoza et al, 2022 ). There is compelling evidence suggesting that GRIK3 participates in cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And Huang et al confirmed that GABRD receptors indicated by T cells directly inhibit CD8 + T cells by participating in signal regulation ( Huang et al, 2022 ). Glutamate ionotropic receptor kainate type subunit 3 (GRIK3) and glutamate receptor ionotropic kainate-5 (GRIK5) are members of the glutamate kainate receptor family and play crucial roles in the neuroactive ligand-receptor interaction pathway ( Fang et al, 2021 ; Minoza et al, 2022 ). There is compelling evidence suggesting that GRIK3 participates in cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Xiao et al found that GRIK3 promotes epithelial-mesenchymal transition in breast cancer cells by regulating SPDEF/CDH1 signaling ( Xiao et al, 2019 ). Furthermore, GRIK5 has been identified as a potential biomarker for melanoma metastatic progression ( Minoza et al, 2022 ). Although limited research exists on the relationship between GRIK5 expression and colorectal cancer (CRC), our study fills this gap by identifying a significant association between high GRIK5 expression and CRC progression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the boundary between predictive and prognostic biomarkers is usually unclear, so when people discover a new biomarker, it is impossible to categorize it definitively as predictive or prognosis [ 162 ] . To address these challenges, multi-omic approaches, such as integrating genomics, transcriptomics, and proteomics data, are employed to identify comprehensive biomarker signatures [ 163 , 164 ] . Machine learning algorithms and artificial intelligence are also used to analyze large datasets and uncover novel associations between biomarkers and treatment responses [ 165 , 166 ] .…”
Section: Molecular Biomarkers Of Immunotherapymentioning
confidence: 99%
“…The details of biomarker assessment methodologies are presented in Supplemental Table S2. Studies investigating K17 at the transcriptome level (n = 24) have found K17 to hold negative prognostic value in most cancer entities (endometrial [30,71], esophageal [57], gastric [72], HNSCC [38,42,52], lung cancer [73,74], melanoma [75,76], pancreatic adenocarcinoma [50,51], and renal cell carcinoma [77]). In TNBC, a negative correlation between K17 RNA expression and outcome was found only in a subgroup of patients with invasive ductal carcinoma with large tumors and advanced stage [29].…”
Section: Prognostic Significancementioning
confidence: 99%
“…The detailed characteristics and key findings of prognostic transcriptome-based studies are presented in Table 4 and Table S4. Thirteen studies (56.5%) were based on data derived from The Cancer Genome Atlas (TCGA) [30,31,49,50,57,71,71,73,75,76,80]. Five studies (21.7%) generated their own transcriptome data [38,42,51,52,79].…”
Section: Prognostic Significancementioning
confidence: 99%